Cyprinodontiform fishes of El Salvador (UNED Research Journal, 2021)
Introduction: The Cyprinodontiformes are a group of secondary freshwater fishes widely distributed in El Salvador. Currently, many species of this group are usually incorrectly identified for lack of adequate tools. Additionally, their taxonomy and distribution have changed in recent years. Objective: To provide updated information about the taxonomy and distribution of El Salvador Cyprinodontiformes through identification keys, distribution notes, and general descriptions for all species. Methods: We carried out an extensive review of the literature, electronic databases, and museum specimens to generate a list of valid species present in El Salvador. Results: Eleven species in three families are confirmed: Profundulidae (two species), Anablepidae (one species), and Poeciliidae (eight species). We also include distribution data, both vertical and by main basins, and an illustrated guide. Conclusions: There are 11 species of Cyprinodontiformes in El Salvador and they can be found and identified with this article.
Keywords: Profundulidae; Anablepidae; Poeciliidae; Central America; Distribution; Taxonomic Key